If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -3 = 5x + -4 Reorder the terms: -3 + 6x = 5x + -4 Reorder the terms: -3 + 6x = -4 + 5x Solving -3 + 6x = -4 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -3 + 6x + -5x = -4 + 5x + -5x Combine like terms: 6x + -5x = 1x -3 + 1x = -4 + 5x + -5x Combine like terms: 5x + -5x = 0 -3 + 1x = -4 + 0 -3 + 1x = -4 Add '3' to each side of the equation. -3 + 3 + 1x = -4 + 3 Combine like terms: -3 + 3 = 0 0 + 1x = -4 + 3 1x = -4 + 3 Combine like terms: -4 + 3 = -1 1x = -1 Divide each side by '1'. x = -1 Simplifying x = -1
| 4x+28+x+24-8x+20=15x-6 | | 5/2+2m/9=59/18 | | 10x+3=11+8x+19 | | 96-45-x=45 | | .6(10x-2)+3=2-(3x+4) | | -1+1x=5 | | 60+4x-1=6x+11 | | 4t+10s=250 | | 31+7x=16 | | 4x^2-33x+33=-9+6 | | (2x-7)=117 | | 3x-3-2x+2=5 | | 5=7-2 | | 12+5p=6p+12 | | 8v+5=7v+17 | | X^4+4x^3=12x^2 | | 1m=12.4 | | (15x-5)=(90-4x) | | 14+2x=7x-11 | | 4x^5-11=-20491 | | tnx=1.5 | | 8(a-2)+7=6-4(a+3) | | (5n+1)(3n-2)=0 | | 12(x+1)=6(2x+1)+6 | | 12X^3+20x^2-15x-25=0 | | -6(w+2)-w-3=-7(w+5)+20 | | 60+2x+y=360 | | (5v-7)(6-v)=0 | | 3p+q^3=7 | | 4y+6x=124 | | 4x+3x=180 | | 16x+4x^2=128 |